The possible usage of konjac gum in ice-cream production - K. Kaan Tekinşen; Ahmet Güner; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
Aim: This investigation was done to determine the effect of konjac gum and combination of the konjac gum with carragenan and xanthan gum the possible usage on the ice-cream production. Materials and Methods: In the research, the control group was formed using only salep with 0.8% and five experimental groups were formed as; only konjac gum with 0.35% and addition of the carragenan and xanthan gum with 10% and 20% proportions of the konjac gum. Analysis of the ice cream mixes before the production and ice cream samples after the production at 1, 15 and 30th day of the storage period were done. Results: Addition of xanthan gum to konjac gum at 10% and 20% reduced the pH value of the ice-cream mix (p<0.05). Viscosity values of the ice-cream mix were found higher (p<0.001) in only konjac gum and konjac gum with the other stabilizers. Addition of 10% carragenan and 10% xanthan gum increased overrun value of ice-cream mix like as seen in mix with salep. First dropping and complete melting time of the ice-cream with only konjac gum and konjac gum having the other stabilizers were found higher (p<0.001). Konjac gum and konjac gum with other stabilizers improved (p<0.001) the colour-appearance, structureconsistency and taste-smell characteristics of the ice-cream. Conclusion: Konjac gum and/or combination of konjac gum with carragenan and xanthan gum at the 10% and 20% levels on the ice-cream production could be an alternative to the salep.